Exploring individuals' behavioral intentions toward donation crowdfunding: evidence from China. Issue 7 (12th August 2019) - Wang, Tao; Li, Yalan; Kang, Minghui; Zheng, Haichao
Abstract : Purpose: The purpose of this paper is to apply the self-determination theory (SDT) to propose a research model that incorporates the SDT framework and contextual variables as determinants and self-identity and social identity as mediating constructs to predict individuals' intentions toward donation crowdfunding in China. Design/methodology/approach: Structural equation modeling is used to analyze the data collected from China. Findings: The results indicate that the self-identity and social identity collectively or separately mediate the effect exerted by the sense of self-worth, face concern, moral obligation, perceived donor effectiveness, social interaction and referent network size on donation intentions. However, there is no evidence supporting the hypothesis connecting moral obligation with self-identity. Practical implications: The study provides suggestions for service providers on how to improve and perfect the functions, and it also provides insights for donation crowdfunding fundraisers on how to increase the success rate. Originality/value: The conclusions of this study provide academics with a more thorough understanding of the driving forces of individual behavior intention toward donation crowdfunding in China. This study further expands the SDT and identity theory in the context of donation crowdfunding, which improves their robustness in explaining behavioral intention. These theories may be an important part of future information system research.